People-Centric and Inclusive Approach to Planning of Smart Cities - Jakonen, Olli (CSID Journal of Infrastructure Development, 2023)
The smart city continues from intelligent, creative, and sustainable urban development imaginaries and started as a technologically oriented urban development framework. Since its conception, debates between academics, planning practitioners, and private firms have expanded and questioned original notions of ‘smart’ to consider people-centeredness, participation, and inclusion themes broadly. These discussions in smart cities have pointed to a need to question and revise many of the aims, approaches, and methods related to smart urban development. This review asks what elements and factors could be required for a city to be considered smart and people centric. The participatory design enabled by digital tools, a holistic appreciation of place-specific complexities, and considerations of how different demographics can appropriate ‘smartness’ as part of their everyday lives could be considered as such factors. Alongside describing participatory design principles more broadly, this paper considers the case of aging and seniors as an example of a group often viewed as deviating from the “average” user. This demographic often does not benefit from smart city design approaches targeting the “average” city user. Furthermore, the paper considers the potential pitfalls of participatory approaches.